2020
DOI: 10.1017/neu.2020.16
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of clinical conditions commonly associated with mitochondrial disorders in schizophrenia

Abstract: Objective: It has been hypothesized that neuropsychiatric symptoms, including psychosis, can be the result of a milder brain bioenergetic defect produced by mitochondrial dysfunction; however, mitochondrial dysfunction can be present in other organs or systems. The aim of the study was to investigate whether clinical conditions associated with mitochondrial disorders (CAMDs) were frequently present in schizophrenia. Methods: A previously used questionnaire regarding the CAMDs was adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Most studies have found that schizophrenic patients are more likely to have constipation symptoms than healthy people. The main reason is that schizophrenic patients can't control their living habits, and during hospitalization, they don't participate in activities for a long time, which leads to the decrease of body digestive function and eventually constipation [4][5] . Schizophrenia can be divided into positive symptoms and negative symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have found that schizophrenic patients are more likely to have constipation symptoms than healthy people. The main reason is that schizophrenic patients can't control their living habits, and during hospitalization, they don't participate in activities for a long time, which leads to the decrease of body digestive function and eventually constipation [4][5] . Schizophrenia can be divided into positive symptoms and negative symptoms.…”
Section: Introductionmentioning
confidence: 99%